The Existence of the Quarter Life Crisis Phenomenon in Young Adults on Post-Covid-19 Mental Health in Parepare City Communities - M. Nasir; Muhammad Wajdi; Abidin Abidin; Edi Hasan (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This study aims to explore the phenomenon of Quarter Life Crisis among young adults in Parepare City before and after the Covid-19 pandemic and its impact on mental health. This ex-post facto research involved young adults without permanent jobs in Parepare City. A purposive sampling technique was employed, with a total sample of 300 respondents. The study results indicate a significant effect of Quarter Life Crisis on Covid-19 prevention (Sig. 0.002 < 0.005) and on mental health (Sig. 0.014 < 0.05). A mental health workshop is proposed as an intervention to assist individuals experiencing a Quarter Life Crisis.